Student Intrinsic Motivation for Online Creative Idea Generation: Mediating Effects of Student Online Learning Engagement and Moderating Effects of Teacher Emotional Support - Wang, Li (Frontiers in Psychology, 2022)
The online creativity generation research is a new field of creativity research. However, very little is known about the specific psychological processes of online idea generation. Against this background, this study explored the correlation between student intrinsic motivation and online creativity and possible mechanisms that may lie within this relationship. A sample of 423 Chinese students from three public universities participated in this study by completing measurements of intrinsic motivation, online learning engagement, creativity, and perceived teacher emotional support. The results indicated that student online learning engagement partially mediates the positive association between student intrinsic motivation and their online creativity. Teacher emotional support moderates the positive relationship between student intrinsic motivation and online learning engagement. Our findings suggested that student online creativity benefited from their intrinsic motivation in an online environment. The limitations of this study were also discussed.